DEAF1 Binds Unmethylated and Variably Spaced CpG Dinucleotide Motifs - Jensik, Philip J.; Vargas, Jesse D.; Reardon, Sara N.; Rajamanickam, Shivakumar; Huggenvik, Jodi I.; Collard, Michael W. (PloS one, 2014)
DEAF1 is a transcriptional regulator associated with autoimmune and neurological disorders and is known to bind TTCG motifs. To further ascertain preferred DEAF1 DNA ligands, we screened a random oligonucleotide library containing an "anchored" CpG motif. We identified a binding consensus that generally conformed to a repeated TTCGGG motif, with the two invariant CpG dinucleotides separated by 6-11 nucleotides. Alteration of the consensus surrounding the dual CpG dinucleotides, or cytosine methylation of a single CpG half-site, eliminated DEAF1 binding. A sequence within the Htr1a promoter that resembles the binding consensus but contains a single CpG motif was confirmed to have low affinity binding with DEAF1. A DEAF1 binding consensus was identified in the EIF4G3 promoter and ChIP assay showed endogenous DEAF1 was bound to the region. We conclude that DEAF1 preferentially binds variably spaced and unmethylated CpG-containing half-sites when they occur within an appropriate consensus.